Recognition memory in Alzheimer's disease: A demonstration of a remarkable memory capacity in Alzheimer's disease - KARLSSON, Thomas; JOHANSSON, Inez; ADOLFSSON, Rolf; NILSSON, Lars-Göran; DUBUC, Severine (Dementia and geriatric cognitive disorders, 2003)
A compelling feature of human memory is its striking capacity. Under certain circumstances, subjects can remember large amounts of information even with brief exposure at study. This investigation shows that this ability is preserved even in severely impaired Alzheimer's disease patients, and this holds implications for the clinical management of amnesic patients. To this date, demonstrations of preserved learning and memory capacity in Alzheimer's disease and amnesia have been confined to implicit memory tasks. Since the present results were obtained in an explicit memory task, the finding also holds implications for the understanding of amnesia.